Synergistic Antibacterial Activity of Designed Trp-Containing Antibacterial Peptides in Combination With Antibiotics Against Multidrug-Resistant Staphylococcus epidermidis - Shang, Dejing; Liu, Yue; Jiang, Fengquan; Ji, Fangyu; Wang, He; Han, Xue (Frontiers in Microbiology, 2019)
Multidrug resistance among various bacterial strains is leading to worldwide resistance to a wide range of antibiotics. Reviving the therapeutic potential of current antibiotics represents an attractive novel strategy. In this study, we investigated the synergistic antibacterial activity between a series of Trp-containing antimicrobial peptides (AMPs) and four classes of traditional chemical antibiotics that are inactive against multidrug-resistant Staphylococcus epidermidis (MRSE) in vitro and in vivo. Among the antibiotics that we studied, penicillin, ampicillin and erythromycin showed a distinct synergistic effect in combination with all of the Trp-containing AMPs, represented by a fractional inhibitory concentration index (FICI) of <0.5. The antibacterial activities were noticeably improved, with 32-64-fold reduced MIC values for ampicillin and 16-32-fold reduced MIC values for erythromycin and penicillin. Tetracycline showed synergistic activity with only I1WL5W but additive activity with L11W, L12W and I4WL5W. Ceftazidime exhibited additive activity with the Trp-containing peptides. In addition to inhibiting the growth of planktonic bacteria, the peptide and antibiotic combinations significantly reduced biofilm formation of MRSE 1208. A mechanistic study demonstrated that the Trp-containing peptides, especially I1WL5W and I4WL5W with two tryptophan residues, disrupted bacterial inner and outer membranes, which promoted antibiotic delivery into the cytoplasm and access to cytoplasmic targets, but L11W and L12W may increase intracellular antibiotic concentrations by decreasing blaZ, tet(m) and msrA expression. Importantly, a strong synergistic activity was observed for the combination of I1WL5W and penicillin against the MRSE 1208 strain in a mouse infection model. Thus, the combination of AMPs and traditional antibiotics could be a promising option for the prevention of acute and chronic infections caused by MRSE.